PT320, Sustained-Release Exendin-4, Mitigates L-DOPA-Induced Dyskinesia in a Rat 6-Hydroxydopamine Model of Parkinson’s Disease - Yu, Seong-Jin; Chen, Shuchun; Yang, Yung-Yung; Glotfelty, Elliot J.; Jung, Jin; Kim, Hee Kyung; Choi, Ho-Il; Choi, Doo-Sup; Hoffer, Barry J.; Greig, Nigel H.; Wang, Yun (Frontiers in Neuroscience, 2020)
Background We previously demonstrated that subcutaneous administration of PT320, a sustained-release (SR) form of exendin-4, resulted in the long-term maintenance of steady-state exenatide (exendin-4) plasma and target levels in 6-hydroxydopamine (6-OHDA)-pretreated animals. Additionally, pre- or post-treatment with PT320 mitigated the early stage of 6-OHDA-induced dopaminergic neurodegeneration. The purpose of this study was to evaluate the effect of PT320 on L-3,4-dihydroxyphenylalanine (L-DOPA)-induced abnormal involuntary movements (AIMs) in the rat 6-OHDA model of Parkinson’s disease. Methods Adult male Sprague–Dawley rats were unilaterally lesioned in the right medial forebrain bundle by 6-OHDA. L-DOPA and benserazide were given daily for 22 days, starting from 4 weeks after lesioning. PT320 was co-administered weekly for 3 weeks. AIM was evaluated on days 1, 16, and 22 after initiating L-DOPA/benserazide + PT320 treatment. Brain tissues were subsequently collected for HPLC measurements of dopamine (DA) and metabolite concentrations. Results L-DOPA/benserazide increased AIMs of limbs and axial as well as the sum of all dyskinesia scores (ALO) over 3 weeks. PT320 significantly reduced the AIM scores of limbs, orolingual, and ALO. Although PT320 did not alter DA levels in the lesioned striatum, PT320 significantly attenuated 6-OHDA-enhanced DA turnover. Conclusion PT320 attenuates L-DOPA/benserazide-induced dyskinesia in a 6-OHDA rat model of PD and warrants clinical evaluation to mitigate Parkinson’s disease in humans.